2019
DOI: 10.1111/vsu.13353
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo comparison of barbed sutures for pelvic flexure enterotomy in horses

Abstract: Objective To evaluate two different barbed sutures for closure of pelvic flexure enterotomies and compare results achieved with two previously described closure techniques. Study design Ex vivo. Sample population Twenty‐four fresh cadaver adult equine large colons. Methods Cadavers were randomly assigned to four closure groups (n = 6 each group): single‐layer absorbable suture, double‐layer absorbable suture, single‐layer unidirectional barbed suture, or single‐layer bidirectional barbed suture. Construction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…For canine enterotomy closure, Ehrhart et al, placed the effector at the beginning of the incisional line (0 mm), however, it should be noted that the effector loop in this study was placed intraluminally with only a limited description of how the barbed suture line was initiated. In studies by Duffy et al, 24 and Sinovich et al, 30 investigators placed effector loops at 5 mm from the beginning of the incisional line in dogs and horses, respectively 22,30 . In the present study, mean ILPs in the group 5, 10, and 15 mm were significantly higher than the 0 mm group.…”
Section: Discussionsupporting
confidence: 43%
“…For canine enterotomy closure, Ehrhart et al, placed the effector at the beginning of the incisional line (0 mm), however, it should be noted that the effector loop in this study was placed intraluminally with only a limited description of how the barbed suture line was initiated. In studies by Duffy et al, 24 and Sinovich et al, 30 investigators placed effector loops at 5 mm from the beginning of the incisional line in dogs and horses, respectively 22,30 . In the present study, mean ILPs in the group 5, 10, and 15 mm were significantly higher than the 0 mm group.…”
Section: Discussionsupporting
confidence: 43%
“…Despite barbed sutures being more expensive than its conventional counterparts 10 , three studies have shown that the use of barbed sutures reduced the time in the operating room in patients who have undergone spinal surgery 20 and total knee arthroplasty 21,22 . The same studies reported that the reduction in the time spent in the operating room was associated with a decrease in the final cost of the procedures.…”
Section: Discussionmentioning
confidence: 99%
“…One-layer inverting Cushing constructs, investigated ex vivo, had bursting pressures higher than intraluminal colonic pressures recorded in vivo (up to 58 mmHg; Aldrich et al, 2017;Gandini et al, 2013;Sinovich et al, 2020). In two studies, bursting pressures were the same or lower than those of two-layer closures (Aldrich et al, 2017;Gandini et al, 2013;Sinovich et al, 2020). As expected, one-layer closures were faster to perform than two layers in all studies, but luminal diameter reduction was not statistically different between constructs.…”
Section: Hand-sewn One-layer Closuresmentioning
confidence: 99%
“…Other described closure techniques include a one‐layer Utrecht (Young et al., 1991), one‐layer Cushing (Aldrich et al., 2017; Gandini et al., 2013), two‐layer with suture reversal (Aldrich et al., 2017), double inverting closure (Doyle et al., 2003), three‐layer closure (Marien et al., 2000; Young et al., 1991), thoracoabdominal stapling device (Ellis et al., 2007; Gandini et al., 2013; Rosser, Brounts, Livesey, & Wiedmeyer, 2012; Rosser, Brounts, Slone, et al., 2012), skin staples (Gandini et al., 2013) and one‐layer seromuscular Cushing with barbed sutures (Sinovich et al., 2020).…”
Section: Closure Techniquesmentioning
confidence: 99%